2008
DOI: 10.1111/j.1476-5381.2008.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the phosphatase PTEN protects mice against oleic acid‐induced acute lung injury

Abstract: Background and purpose: Injury to the lung parenchyma is a constitutional feature shared by many lung diseases. The protein, phosphatase and tensin homologue deleted on chromosome Ten (PTEN) is a major suppressor of phosphoinositide-3 kinase/Akt signalling, a vital survival pathway in lung parenchymal cells. Based on this, we hypothesized that PTEN inhibition in vivo would enhance cell tolerance to stress thereby preventing acute lung injury. Experimental approach: We evaluated the ability of a PTEN inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…The S370 residue of PTEN is phosphorylated by casein kinase 2 (CK2), and this phosphorylation reduces PTEN activity (36,53). We therefore determined whether bpV(phen), a potent inhibitor of PTEN (32), relieves the effect of TIMAP silencing on Akt phosphorylation. Pilot experiments showed that bpV(phen) increased S473 Akt phosphorylation in a concentration-dependent fashion in TIMAP-depleted and in cells treated with control siRNA, with a maximal effect at a concentration of 20 M (not shown).…”
Section: Inhibition Of Timap Expression Attenuates Ec Proliferation mentioning
confidence: 99%
“…The S370 residue of PTEN is phosphorylated by casein kinase 2 (CK2), and this phosphorylation reduces PTEN activity (36,53). We therefore determined whether bpV(phen), a potent inhibitor of PTEN (32), relieves the effect of TIMAP silencing on Akt phosphorylation. Pilot experiments showed that bpV(phen) increased S473 Akt phosphorylation in a concentration-dependent fashion in TIMAP-depleted and in cells treated with control siRNA, with a maximal effect at a concentration of 20 M (not shown).…”
Section: Inhibition Of Timap Expression Attenuates Ec Proliferation mentioning
confidence: 99%
“…21 Rat lung tissue was exposed and different groups of rat lung gross morphology pictures were obtained. Representative lung tissue sections from 2 and 6 h after surgery (n ¼ 7 animals per group) were fixed in 4% formaldehyde, and were prepared for H&E staining following routine methods.…”
Section: Assessment Of Alimentioning
confidence: 99%
“…Thus, to facilitate further study of PTPMT1 and its role in ␤-cell metabolism in particular, we undertook a search for inhibitors of the enzyme. There is good precedence for the use of smallmolecule inhibitors of phosphatases in the interrogation of the biology of these enzymes, and selective inhibitors of phosphatases may well prove valuable in the treatment of diseases affected by their dysregulation (Lai et al, 2009).…”
mentioning
confidence: 99%